Revised Ordinances of the City of Salina 99 (1879) - (:unkn) unknown (My University, 1879)
That it shall be unlawful for any person to carry on or about his person any pistol, bowie knife, dirk, or other deadly or dangerous weapon, anywhere within the limits of the city of Salina, save and except as hereinafter provided.
Keywords: CARRY